Program Tabung Sampah Bersih (TASBIH): Prospek dan Aspek Pemberdayaan Lansia Di Yayasan Pitutur Luhur Banyu Biru Kabupaten Semarang - Suprihatiningsih Suprihatiningsih; Roissatul Ngulum (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
The elderly guidance carried out by the Pitutur Luhur Foundation aims to provide guidance, empowerment and motivation to the elderly to keep empowered and useful up to their older ages.  Empowering the elderly is done in various ways, one of which is by using the Clean Waste Savings (TASBIH) program to empower the elderly to care about the environment and provide waste management skills to the elderly.  This research is a qualitative research with a social psychology approach.  Data collection techniques used in the research are interviews, observation and documentation.  Data analysis used in this study is data reduction, data presentation and conclusion drawing. The results of this study indicate that the empowerment of the elderly through the TASBIH program carried out by the Pitutur Luhur Gedong Foundation, Banyubiru District, Semarang Regency is carried out through several stages, namely: The awareness stage is carried out through learning with Thaharoh fiqh material, socialization of waste sorting and healing of the Qur'an, (2) Capacity building with religious training activities such as Tadabur Alam in the Gadjah Mungkur Mountains of Banyu Biru Regency, Semarang, making brooches from plastic waste, making doormats from  used cloth, making flowers from plastic, making drink packaging bags and making flower pots from used towels and (3) the Evaluation Phase was carried out by the Tasbih Tube administrator and involved some participants. Based on the empowerment stage and the results of the empowerment of the elderly at the Pitutur Luhur Foundation, the elderly are able to be empowered in managing waste, making crafts from waste according to the abilities obtained during the capacity building stage.  In addition, by empowering the elderly through the TASBIH program, the elderly regain their motivation and enthusiasm to continue empowered and productive in old age